ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP IMPLEMENTASI TARGET ENERGI TERBARUKAN DALAM ASEAN TOTAL MIX ENERGY DI DALAM APAEC PERIODE 2016-2025 - Alynka Putri Adhitama (2023)
One of the attempts to increase energy security, namely energy diversification, can be carried out through an energy transition to renewable energy. ASEAN as a country with a high level of economic growth requires a large supply of energy. This large demand for energy supply can be met through fossil energy and renewable energy. Given the environmental crisis that has occurred as a result of the production and consumption of fossil energy, there is a concern about the need for change toward clean, renewable energy that is sustainable. In its efforts to improve energy security and encourage energy transition, ASEAN member countries within the framework of the energy cooperation policy they made, namely the ASEAN Plan of Action for Energy Cooperation (APAEC) 2016-2025 set an aspirational target of increasing the share of the renewable energy sector by 23% in ASEAN total energy mix by 2025. However, the existence of the COVID-19 pandemic has had a major impact on various sectors of people's lives, including the energy sector. This research will discuss the impact of the COVID-19 pandemic on the effort of energy transition to renewable energy. How the COVID-19 pandemic affecting the efforts to implement renewable energy targets in the ASEAN region. This study uses a descriptive qualitative methodology to explain the research topic above. This research will also look at the policies required by ASEAN member countries (AMS) to achieve the renewable energy targets that have been determined.